Pengaruh Styrofoam sebagai Bahan Tambah dalam Campuran Laston Lapis Antara - Richard Marcelenus Pasapan; Nur Ali; Rais Rachman (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This research is intended to test the use of Styrofoam as an additive in the mixture of Laston Lapis Antara.The methodology used is the design of the Intermediate Laston mixture design and the Marshall immersion test for the characteristics of the mixture. The results of the research through the conventional Marshall test, obtained a mixture of Laston Lapis Antara with Styrofoam content, namely 0%, 1%, 2%, 3%, 4% with an asphalt content of 5.0% meeting the requirements of the 2018 Highways standard. The results of testing the characteristics of the Conventional Marshall Mix of Laston Layer Between with added Styrofoam ingredients are that if the Styrofoam content increases, the VIM, Flow and VMA values decrease at each Styrofoam level, while the Stability and VFB values increase. The effect of adding Styrofoam can improve the performance of the Laston Lapis Antara mixture, where the stability value increases and the meltdown decreases.